Droplet microfluidics for lab-on-a-chip devices. - Lee, Stanley Jun Jie. (2013)
This project involves the complete process of soft lithography for creating lab-on-a-chip devices for droplet generation. The micro-droplets of about 50μm can be used for single cell encapsulation as a micro-reactor to study cell growth, cell secretion, cell-cell interaction and therapeutic agent reactions.